Unintentional injuries among refugee and immigrant children and youth in Ontario, Canada: a population-based cross-sectional study. Issue 5 (25th September 2017) - Saunders, Natasha Ruth; Macpherson, Alison; Guan, Jun; Guttmann, Astrid
Abstract : Background: Unintentional injuries are a leading reason for seeking emergency care. Refugees face vulnerabilities that may contribute to injury risk. We aimed to compare the rates of unintentional injuries in immigrant children and youth by visa class and region of origin. Methods: Population-based, cross-sectional study of children and youth (0–24 years) from immigrant families residing in Ontario, Canada, from 2011 to 2012. Multiple linked health and administrative databases were used to describe unintentional injuries by immigration visa class and region of origin. Poisson regression models estimated rate ratios for injuries. Results: There were 6596.0 and 8122.3 emergency department visits per 100 000 non-refugee and refugee immigrants, respectively. Hospitalisation rates were 144.9 and 185.2 per 100 000 in each of these groups. The unintentional injury rate among refugees was 20% higher than among non-refugees (adjusted rate ratio (ARR) 1.20, 95% CI 1.16, 1.24). In both groups, rates were lowest among East and South Asians. Young age, male sex, and high income were associated with injury risk. Compared with non-refugees, refugees had higher rates of injury across most causes, including for motor vehicle injuries (ARR 1.51, 95% CI 1.40, 1.62), poisoning (ARR 1.40, 95% CI 1.26, 1.56) and suffocation (ARR 1.39, 95% CI 1.04, 1.84). Interpretation: The observed 20% higher rate of unintentional injuries among refugees compared with non-refugees highlights an important opportunity for targeting population-based public health and safety interventions. Engaging refugee families shortly after arrival in active efforts for injury prevention may reduce social vulnerabilities and cultural risk factors for injury in this population.